Plasma proteins as prognostic biomarkers in radiotherapy treated head and neck cancer patients. (February 2017) - Brøndum, Line; Eriksen, Jesper Grau; Singers Sørensen, Brita; Mortensen, Lise Saksø; Toustrup, Kasper; Overgaard, Jens; Alsner, Jan
Abstract: Background: Blood-based protein biomarkers can be a useful tool as pre-treatment prognostic markers, as they can reflect both variations in the tumor microenvironment and the host immune response. We investigated the influence of a panel of plasma proteins for the development of any failure defined as recurrent disease in the T-, N-, or M-site in HNSCC. Methods: We used a multiplex bead-based approach to analyze 19 proteins in 86 HNSCC patients and 15 healthy controls. We evaluated the associations between the biomarkers, loco-regional failure, failure in the T-, N-, or M-site, overall survival (OS), p16 status, and hypoxia. Results: In 41 p16 positive oropharynx cancer patients we identified a profile of biomarkers consisting of upregulation of IL-2, IL-4, IL-6, IL-8, eotaxin, GRO-a, and VEGF and downregulation of VEGFR-1 and VEGFR-2 with a significantly reduced risk of failure ( p < 0.01). None of the individual proteins were associated with outcome. Conclusion: The identified plasma profile potentially reflects an activated immune response in a subgroup of the p16 positive patients.